Big Data e Processamento de Dados: Uma Jornada para a Descoberta de Insights - MATEUS BARBOSA CASSIANO (2024)
This work aims to explore how the use of Big Data techniques, combined with the ETL (Extract, Transform, Load) process, can transform large volumes of data into valuable insights to enhance the user experience. With the exponential growth of data generation in the digital age, driven by connected devices, social networks, and streaming services, the proper handling of this data is crucial for generating insights and supporting strategic decision-making. The results demonstrate the effectiveness of the process in creating an interactive dashboard, where users can explore music and artist rankings based on various metrics, view graphs, and customize filters according to their preferences. This approach made it possible to highlight trends between different musical genres through data analysis. The work successfully simulated a Big Data scenario and showed how the structured use of data can generate value. Proper data handling not only improves the user experience but also has the potential to revolutionize the use of information across various sectors.